Hypoabsorption in Bariatric Surgery: Is the Benefit Worth the Risk? - Tala Abedalqader; Noura Jawhar; Aryan Gajjar; Ray Portela; Gerardo Perrotta; Nour El Ghazal; Simon J. Laplante; Omar M. Ghanem (Medicina)
Metabolic and bariatric surgery has been well described in the existing literature to be an effective and safe modality for weight loss in patients with obesity. Recently, hypoabsorptive procedures such as one-anastomosis gastric bypass (OAGB), biliopancreatic diversion with duodenal switch (BPD-DS), and single-anastomosis duodenoileostomy with sleeve (SADI-S) have gained traction, particularly among patients with severe obesity. These procedures combine restrictive and hypoabsorptive mechanisms, resulting in significant and sustainable weight loss, especially in those with severe obesity and associated comorbidities. However, the risk of malnutrition and nutritional deficiency following these procedures has been a deterrent for surgeons in their adoption. This review evaluates the existing literature on the safety, efficacy, and long-term outcomes of OAGB, BPD-DS, and SADI-S. While these hypoabsorptive procedures represent highly effective options for treating obesity, the associated nutritional complications necessitate the need for long-term follow-up and supplementation and highlight the need for careful patient selection.